National Audubon Society first field guide. Birds - Weidensaul, Scott; National Audubon Society (New York : Scholastic, 1998)
Provides an overview of birds, with specific information on over 150 species found in North America.
Includes bibliographical references (p. 152-153) and index.
Wilson's Junior High School.
5.9
3-6
Keywords: Birds -- Juvenile literature; Birds -- Identification -- Juvenile literature; Birds -- North America -- Identification -- Juvenile literature; Birds; Birds -- Identification; Birds; Birds -- Identification; Birds; Birds -- North America